5xy平方+3x平方y-xy平方-2x平方y-1 合并同类项
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 22:00:22
5xy平方+3x平方y-xy平方-2x平方y-1合并同类项5xy平方+3x平方y-xy平方-2x平方y-1合并同类项5xy平方+3x平方y-xy平方-2x平方y-1合并同类项=5xy^2+3x^2y-
5xy平方+3x平方y-xy平方-2x平方y-1 合并同类项
5xy平方+3x平方y-xy平方-2x平方y-1 合并同类项
5xy平方+3x平方y-xy平方-2x平方y-1 合并同类项
=5xy^2+3x^2y-xy^2-2x^2y-1
=(5xy^2-xy^2)+(3x^2y-2x^2y)-1
=4xy^2+x^2y-1
=4xy平方+x平方y-1
3x平方-5x平方y-{2x平方y+6xy平方-[2xy平方-3x平方y+(3x平方y-4xy平方】}
初一2x平方-5xy-3x平方+4y平方+3xy-y平方
5xy平方+3x平方y-xy平方-2x平方y-1 合并同类项
2x平方y-2xy+3xy平方+5+2xy+x平方y-3xy平方-3 过程!
(3X平方-5Y)+[-3XY-2(X平方-XY)+Y平方]
计算 5xy的平方-【3xy的平方-(4xy的平方-2x的平方y)】+2x的平方y-xy的平方
(2xy平方+3xy平方)-(6x平方y-3xy平方)=
计算:(x平方+y平方/xy-x平方/xy+y平方-y平方/x平方+xy)除以3/xy
2x平方y+3x平方Y-2XY平方+2XY+XY是多少啊
(3x平方-4y平方)+[-(x平方-2xy-y平方)]-[(3x平方-2xy-y平方)]
(2x平方y+3xy平方)-(6x平方y-3xy平方)等于多少
-3x平方-4xy-6xy-(-y平方)-2x平方-3y平方求值
x平方+3xy+2y平方/x平方y+2xy平方
5xy平方-2x平方y+[3xy平方-(4xy-2x平方y-2x平方y)],其中x=-2,y=-1求值
(2X平方y+3xy平方)-(6x平方-3XY平方)(计算)
2x平方-5xy-3y平方 因式分解
2x平方-3xy-5y平方
化简-(x平方-2xy-y平方)+(5x平方-2xy-3y平方)